Electrochemical Analysis of Methanol with Nafion-Coated Copper Oxide Nanoparticles - Pantipa Sawatmuenwai; Keerakit Kaewket; Kamonwad Ngamchuea (Journal of Analytical Methods in Chemistry)
This work introduces a Nafion-coated copper(I) oxide nanoparticle electrode (Nafion/Cu2O/GC) designed for the electrochemical detection of methanol (CH3OH). The responses of the composite material toward CH3OH were enhanced by the selective permeation of CH3OH through the hydrophilic channels of the Nafion membrane in combination with the electroactivity of Cu2O nanoparticles. The sensor displayed a linear detection range of 0.33–100 mM CH3OH with a sensitivity of 0.17 μA·mM−1 and a detection limit (3 s/m) of 0.10 mM. It exhibited excellent reproducibility with a relative standard deviation of <5%. The sensor’s practical applicability was demonstrated through recovery studies on hand sanitizer samples, achieving ca. 100% recovery. The sensor was further used to elucidate CH3OH adsorption on activated carbon, revealing that the process conforms to the Langmuir isotherm model.